(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: To describe the current state of anxiety disorders among caregivers of psychiatric patients being treated at a psychiatric hospital in Dak Lak province in 2023. Subject and methods: A cross-sectional descriptive study design was performed on 167 caregivers of psychiatric patients. Results: The prevalence of anxiety disorders among caregivers of psychiatric patients is 46.7%. In which mild anxiety disorder is 94.8%, moderate level is 3.9% and severe is 1.3%. The burden encountered by carers is mainly financial burden with 83.2%, reducing or stopping interaction with neighbors (62.3%), family becoming isolated (52.1%), and affecting relationships in the family (47.3%). Caregiver concerns include fear that the patient will get sicker (98.8%), economic impact (83.8%), ineligibility for treatment (81.4%), effect on children (80.8%). The majority of caregivers receive help in the care of psychiatric patients on an occasional (60.5%) and regular (28.7%) level. Day care hours for caregivers of psychiatric patients are 7 hours and caregivers care days a week are 5 days. Conclusion: Nearly half of caregivers of psychiatric patients have an anxiety disorder. Families and healthcare workers need to be more attentive to caregivers’ mental health.